Social selling : techniques to influence buyers and changemakers - Hughes, Tim, 1965-; Reynolds, Matt, 1974- (Kogan Page, 2016)
"The digital landscape has changed buyers' habits. Sales professionals now need to develop relationships with decision-makers through social networks to reach them early in the decision making process.Social Sellingprovides a practical, step-by-step outline for harnessing the skills and techniques necessary to achieve this, including developing a high quality community, building trust, developing authority and influence, and connecting with changemakers. It also discusses enterprise implementation of a social selling strategy, maturity and investment models necessary, risk and governance, and technology platforms. The chapters feature tips, checklists, and theoretical examples"--Resumé vydavatele